2018
DOI: 10.1007/s10555-018-9749-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytochrome P450-dependent cancer cell mitochondria: cancer associated CYPs and where to find them

Abstract: While cytochrome P450 (CYP)-mediated biosynthesis of arachidonic acid (AA) epoxides promotes tumor growth by driving angiogenesis, cancer cell intrinsic functions of CYPs are less understood. CYP-derived AA epoxides, called epoxyeicosatrienoic acids (EETs), also promote the growth of tumor epithelia. In cancer cells, CYP AA epoxygenase enzymes are associated with STAT3 and mTOR signaling, but also localize in mitochondria, where they promote the electron transport chain (ETC). Recently, the diabetes drug metfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…As mentioned above, sEH hydrolyzes EETs to corresponding diols [Jiang et al, 2005;Harris and Hammock, 2013]. Previous studies reported that EETs stimulate proliferation activity and inhibit apoptosis via activation of ERK1/2 and PI3K/Atk pathways [Yang et al, 2007;Dhanasekaran et al, 2008;Shen et al, 2008;Batchu et al, 2011;Guo et al, 2018]. Contrary to the studies mentioned above, it has been proven that EETs decreased the proliferation of murine fibroblasts [Nieves and Moreno, 2007;Sirish et al, 2013].…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned above, sEH hydrolyzes EETs to corresponding diols [Jiang et al, 2005;Harris and Hammock, 2013]. Previous studies reported that EETs stimulate proliferation activity and inhibit apoptosis via activation of ERK1/2 and PI3K/Atk pathways [Yang et al, 2007;Dhanasekaran et al, 2008;Shen et al, 2008;Batchu et al, 2011;Guo et al, 2018]. Contrary to the studies mentioned above, it has been proven that EETs decreased the proliferation of murine fibroblasts [Nieves and Moreno, 2007;Sirish et al, 2013].…”
Section: Discussionmentioning
confidence: 93%
“…These genes, which signi cantly varied within the three phenotypes, possibly contributed to form the heterogenous TIME of HCC. In addition, many genes have been reported to be critical in immune response, such as CD27, CD8A, GZMA and IL7R [46][47][48][49]. The GO and KEGG annotation also displayed intensive immune phenotypes ( Figure S6A-S6B, Table S10-S11).…”
Section: Methylation Modi Cation and Regulation Of The Time Phenotypesmentioning
confidence: 96%
“…These genes, which signi cantly varied within the three phenotypes, possibly contributed to form the heterogenous TIME of HCC. In addition, many genes have been reported to be critical in immune response, such as CD27, CD8A, GZMA and IL7R [46][47][48][49]. The GO and KEGG annotation also displayed intensive immune phenotypes (Figs.…”
Section: Methylation Modi Cation and Regulation Of The Time Phenotypesmentioning
confidence: 98%